Eksistensi Kosa Kata Bahasa Arab dalam Istilah Ajaran Tarekat Naqsyabandiyah dan Pemikirannya di Lombok - Ali Fathurrahman; Muhammad Amri; Darussalam Syamsuddin; Baiq Raudatussolihah (CV. SINAR HOWUHOWU, 2026)
This study examines the existence of Arabic vocabulary in the teachings of the Naqsyabandiyah Order in Lombok as part of the dynamics of the transmission of Islamic religious traditions in the local context of the Indonesian archipelago. The focus of the study is directed at the Arabic lexical forms used in the terminology of the teachings, rituals, and practices of the Naqsyabandiyah Order and their adaptation process in the language of the Sasak people. The method used is descriptive qualitative with a linguistic-sociological approach, through observation, in-depth interviews, and analysis of the order's teaching documents. The research findings show that many key terms in the Naqsyabandiyah, such as dhikr khafi, talqin, suluk, and mursyid, have undergone a layered process of re-interpretation between Arabic etymological meanings and contextual meanings of Lombok culture. This adaptation does not eliminate the Arabic identity of the vocabulary, but rather strengthens the order's spiritual legitimacy and becomes the religious identity of its community of adherents. Thus, the existence of Arabic vocabulary in Naqsyabandiyah in Lombok is not only linguistic, but also symbolic and cultural, which also influences local religious patterns and the construction of spiritual authority.